2021
DOI: 10.1099/mic.0.001104
|View full text |Cite
|
Sign up to set email alerts
|

Colistin resistance in Escherichia coli confers protection of the cytoplasmic but not outer membrane from the polymyxin antibiotic

Abstract: Colistin is a polymyxin antibiotic of last resort for the treatment of infections caused by multi-drug-resistant Gram-negative bacteria. By targeting lipopolysaccharide (LPS), the antibiotic disrupts both the outer and cytoplasmic membranes, leading to bacterial death and lysis. Colistin resistance in Escherichia coli occurs via mutations in the chromosome or the acquisition of mobilized colistin-resistance (mcr) genes. Bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Bacteria with resistance via spontaneous mutation or acquisition of an mcr gene are still susceptible to outer membrane damage, as assessed using ingress of fluorescent dyes and antibiotics [37, 38]. By contrast, the cytoplasmic membranes of colistin-resistant bacteria are resistant to damage, enabling bacterial survival [37, 38]. This is thought to be due to the presence of large concentrations of unmodified LPS in the outer membrane, whereas the abundance of LPS in the cytoplasmic membrane is so low that even if only a fraction of molecules are modified it is sufficient to confer protection [37, 38].…”
Section: Polymyxin Resistance Via Acquired Genesmentioning
confidence: 99%
See 3 more Smart Citations
“…Bacteria with resistance via spontaneous mutation or acquisition of an mcr gene are still susceptible to outer membrane damage, as assessed using ingress of fluorescent dyes and antibiotics [37, 38]. By contrast, the cytoplasmic membranes of colistin-resistant bacteria are resistant to damage, enabling bacterial survival [37, 38]. This is thought to be due to the presence of large concentrations of unmodified LPS in the outer membrane, whereas the abundance of LPS in the cytoplasmic membrane is so low that even if only a fraction of molecules are modified it is sufficient to confer protection [37, 38].…”
Section: Polymyxin Resistance Via Acquired Genesmentioning
confidence: 99%
“…baumannii can acquire resistance to very high concentrations of colistin via loss of LPS biosynthesis, resulting in outer and cytoplasmic membranes that consist of phospholipid bilayers [39]. Polymyxin-mediated disruption of the cytoplasmic membrane is sufficient to allow ingress of the fluorescent dye propidium iodide [37, 38] and the egress of small molecules such as potassium ions, amino acids and uracil, as well as proteins such as beta-galactosidase [40, 41]. However, it is not clear to what extent the release of these molecules is due to the initial interaction of polymyxins with LPS or the subsequent lysis.…”
Section: Polymyxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In umbrella sampling simulations, Jiang et al show that colistin binding to their LPS-deficient model outer membrane model is energetically unfavourable, due to the lower surface charge relative to LPS-containing bilayers (Jiang et al 2020b) This is in broad agreement with recent work by Edwards and co-workers which has shown that polymyxins pass through the inner membrane by interacting with the small quantities of LPS present in it. (Sabnis et al 2021;Humphrey et al 2021) Zhu et al also perform atomistic simulations of symmetric bilayers representing LPS-deficient A. baumannii membranes with varying proportions of PG lipids (lipids with phosphatidylglycerol headgroup). At PG concentrations >35:65 (PG: other lipids) colistin molecules are found to bind preferentially to the anionic PG lipids, leading to a reduction in lipid lateral diffusion.…”
Section: Dynamics Of Polymyxins In the Inner Membranementioning
confidence: 99%